2010
DOI: 10.1103/physrevlett.104.066101
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Viscosity of the Free Surface in Entangled Polymer Melt Films

Abstract: By embedding "dilute" gold nanoparticles in single polystyrene thin films as "markers", we probe the local viscosity of the free surface at temperatures far above the glass transition temperature (T(g)). The technique used was x-ray photon correlation spectroscopy with resonance-enhanced x-ray scattering. The results clearly showed the surface viscosity is about 30% lower than the rest of the film. We found that this reduction is strongly associated with chain entanglements at the free surface rather than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 20 publications
7
64
1
Order By: Relevance
“…We further investigated the local viscosity of the surface and center regions calculated by the S-E law. Interestingly, we found the well-known relationship of € η ∝ M w 3.4 , which is known as the power law variation for entangled polymers [8], in both the surface and resonance modes [5]. This finding indicates that the polymer chains are indeed entangled even at the surface region within the thickness of 90 Å and the chain dynamics is still governed by the pure reptation mechanism.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…We further investigated the local viscosity of the surface and center regions calculated by the S-E law. Interestingly, we found the well-known relationship of € η ∝ M w 3.4 , which is known as the power law variation for entangled polymers [8], in both the surface and resonance modes [5]. This finding indicates that the polymer chains are indeed entangled even at the surface region within the thickness of 90 Å and the chain dynamics is still governed by the pure reptation mechanism.…”
Section: Resultssupporting
confidence: 54%
“…Resonance-enhanced x-rays (REX), which are generated by the interference of x-ray plane waves reflected and refracted at the two interfaces of the film in air, are significantly intensified at the position close to the center of the film [4]. We found that the resonance enhanced xray intensity at the first resonance mode (i.e., at the incident angle (θ) of 0.168º for a 1280 Å film) is 53.5 times higher than that of the incident beam and the intensity near both interfaces can be eliminated [5]. It should be noted that the incident angle for the first resonance mode depends on the film thickness and second-order (θ=0.184º) and third-order (θ=0.200º) REXs can be also produced within the film.…”
Section: Methodsmentioning
confidence: 83%
“…Hence it is clear that the outof-plane motion of the particle is much slower inside the film. This relatively slower motion is possibly indicative of the enhanced viscosity of the polymer matrix due to the irreversibly adsorbed layers of polymer chains similar to some earlier observations 51,52 . Interestingly, reduced diffusion coefficient of polymer chains normal to the thickness in polymer films was also observed in simulations 53 and the reduced effective mobility of the PGNPs in the direction perpendicular to the film thickness could be indicative of such lower chain diffusivities of confined polymers.…”
Section: X-ray Reflectivitysupporting
confidence: 56%
“…63) Koga et al studied the dynamics of markers in PS thin films, and successfully evaluated the surface viscosity and the internal viscosity independently using resonance-enhanced X-ray scattering technique. 64) …”
Section: X-ray Photon Correlation Spectroscopymentioning
confidence: 99%